Thickness effect on VOC sensing properties of sprayed In2S3 films. Issue 32 (18th May 2020) - Souissi, R.; Bouguila, N.; Bouricha, B.; Vázquez-Vázquez, C.; Bendahan, M.; Labidi, A.
Abstract : The dynamic response of In2 S3 films to 4000 ppm of methanol, ethanol and acetone at 350 °C for thicknesses varying from 0.8 μm to 6.1 μm. Abstract : This work reports the thickness effect on the sensing performances of In2 S3 material for some Volatile Organic Compounds (VOCs). In2 S3 films were deposited on glass substrates by the spray pyrolysis technique. Different samples were prepared via changing the spray time in the range of 10–90 min. The film thickness varies from 0.8 μm to 6.1 μm. The X-ray diffraction results demonstrate that the In2 S3 films are polycrystalline in nature and exhibit a cubic structure. Additionally, Scanning Electron Microscopy (SEM) and 3D profilometry examinations show that the surface roughness increases with the rising spray time. On the other hand, the oxygen adsorption versus working temperature was investigated. Sensing measurements with ethanol, methanol and acetone gases were carried out by a dynamic control of the current passing through the sensitive layers. The best sensitivity was obtained for the film matching a 70 min deposit time. An understanding of the detection mechanism based on the oxidation reaction between reduced vapors and chemisorbed oxygen was confirmed. The selectivity of the sensor was analyzed for several volatile organic compounds (VOCs).